PENGUATAN KARAKTER DALAM PENDIDIKAN KELUARGA MENURUT PANDANGAN KI HAJAR DEWANTARA - Marsono (Guna Widya: Jurnal Pendidikan Hindu, 2018)
Ki Hajar Dewantara said that educating children is educating the people. The circumstances in our life and our livelihood today are the educational fruits we receive from our parents when we were children. Instead of children who at this time we are educated, will someday become our citizens. Intended is the educa- tional instuition still needs to be developed through the themes of thought, espe- cially. The family institution that became the first and main educational environ- ment received the main criteria for putting the educational position as a building to deliver people to the ideals of educational ideal as previously formulated. And that family education will be discussed in this writing.